2021
DOI: 10.3390/w13152037
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Evapotranspiration in Brazilian Cerrado Biome Simulated with the SWAT Model

Abstract: Evapotranspiration represents a significant part on the water balance and, thus, the correct evaluation of this hydrological parcel is relevant when modeling a watershed. The objective of this work is to evaluate the Soil and Water Assessment Tool (SWAT) model’s capability in adequately simulating evapotranspiration in a watershed with predominance of the Brazilian Cerrado biome. Hydrological modeling of the Gama watershed located in the Federal District, which has 57.5% of its total area covered by pristine C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…PPT is the precipitation, ET is the real evapotranspiration and PET is the potential evapotranspiration which was calculated using the Hargreaves method because of the available measured data. Hargreaves has shown to reach acceptable estimations for Cerrado and Amazon Forest (Ferreira et al, 2021; Monteiro et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PPT is the precipitation, ET is the real evapotranspiration and PET is the potential evapotranspiration which was calculated using the Hargreaves method because of the available measured data. Hargreaves has shown to reach acceptable estimations for Cerrado and Amazon Forest (Ferreira et al, 2021; Monteiro et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Hargreaves has shown to reach acceptable estimations for Cerrado and Amazon Forest (Ferreira et al, 2021;Monteiro et al, 2021).…”
Section: Identification and Attribution Of Hydrological Changes In Lo...mentioning
confidence: 99%
“…The model is flexible and extensible, and it is computationally very efficient for doing continuous daily simulations for a longer period. However, the SWAT model cannot accurately simulate real-time crop water requirements (Harikrishna & Sanat, 2020;Navideh et al, 2020;Ferreira et al, 2021;Hanna et al, 2021). Therefore, in this study, the following modifications were made to the SWAT model:…”
Section: Improvement Of the Swat Modelmentioning
confidence: 99%
“…Constant land use changes directly in uence water in ltration into the soil and, consequently, impact the hydrological cycle (Spera et al, 2016). On a global scale, researchers have observed that most hydrological prediction models have been developed and applied in humid and temperate regions (Gao et al, 2016), which leaves a signi cant gap in our understanding of ecohydrological components in savanna regions, especially in neotropical savannas (Ferreira et al, 2021). In the latter case, most publications address topics such as evapotranspiration (Ferreira et al, 2021;Nóbrega et al, 2017), soil water balance (Garcia-Montiel et al, 2008;Oliveira et al, 2015), and land use changes (Hunke et al, 2015).…”
Section: Introductionmentioning
confidence: 99%